2016
DOI: 10.1093/nar/gkw972
|View full text |Cite
|
Sign up to set email alerts
|

Human eIF3b and eIF3a serve as the nucleation core for the assembly of eIF3 into two interconnected modules: the yeast-like core and the octamer

Abstract: The 12-subunit mammalian eIF3 is the largest and most complex translation initiation factor and has been implicated in numerous steps of translation initiation, termination and ribosomal recycling. Imbalanced eIF3 expression levels are observed in various types of cancer and developmental disorders, but the consequences of altered eIF3 subunit expression on its overall structure and composition, and on translation in general, remain unclear. We present the first complete in vivo study monitoring the effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
133
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 69 publications
(152 citation statements)
references
References 53 publications
19
133
0
Order By: Relevance
“…Depletion of individual subunits distinctly affected these processes (Figures 4D–4F). As expected, eIF3a or eIF3g depletion, both of which are essential for cell proliferation, dramatically reduced overall levels of other eIF3 subunits, and decreased the availability of the intact eIF3 holocomplex (Wagner et al, 2014; Wagner et al, 2016). This was reflected by suppression of translation in non-stressed cells, whereby translation was not further decreased upon ER stress induction (Figure 4D).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Depletion of individual subunits distinctly affected these processes (Figures 4D–4F). As expected, eIF3a or eIF3g depletion, both of which are essential for cell proliferation, dramatically reduced overall levels of other eIF3 subunits, and decreased the availability of the intact eIF3 holocomplex (Wagner et al, 2014; Wagner et al, 2016). This was reflected by suppression of translation in non-stressed cells, whereby translation was not further decreased upon ER stress induction (Figure 4D).…”
Section: Resultssupporting
confidence: 74%
“…Depletion of the eIF3l subunit modestly decreased translation in untreated cells without affecting translational recovery during chronic ER stress (Figures 4D and S3C). eIF3l depletion dissociates eIF3k from the eIF3 complex but in human cells, eIF3l is non-essential as fully functional eIF3 complexes form in eIF3l-depleted cells (Wagner et al, 2016). eIF3d depletion, which does not compromise eIF3 complex integrity, or eIF3c knockdown, which breaks eIF3 into at least two subcomplexes (Wagner et al, 2014; Wagner et al, 2016), dramatically reduced translation rates in non-stressed cells (Figure 4D).…”
Section: Resultsmentioning
confidence: 99%
“…The multisubunit factor eIF3 is conserved in eukaryotes. In humans, eIF3 consists of 13 subunits (eIF3a–m), assembled in a macromolecular complex of about 800 kDa, adopting a five‐lobe architecture (Figure b). This factor plays a critical role in cap‐dependent translation via its dual capacity to recruit two fundamental components of the translation machinery, eIF4G and the 40S ribosomal subunit .…”
Section: Relevance Of Rna Structure For Rbp Recognitionmentioning
confidence: 99%
“…Our first FOI was eIF3 since it is the most complex translation initiation factor implicated in promoting numerous reactions throughout the translation cycle (for review see ). We used our robust human eIF3b co-immunoprecipitation protocol (Wagner et al, 2014;Wagner et al, 2016), which efficiently pulls down the entire eIF3 complex, as well as other eIFs and the 40S ( Figure S9A,B). In yeast, we took advantage of the well-established affinity tag pull downs (Nielsen et al, 2006;Valášek et al, 2002), and expressed the genes encoding the Tif32 and Nip1 subunits of eIF3 with a C-terminal FLAG tag from plasmids in a strain deleted for the corresponding genomic wild type allele ( Figure S9C-E).…”
Section: Selective (Sel)-tcp-seq Detects Staged Dissociation Of Eifs mentioning
confidence: 99%
“…The eIF3 complex, composed of five subunits in yeast (a/Tif32, b/Prt1, c/Nip1, g/Tif35, i/Tif34) and twelve in mammals (a, b, c, d, e, f, g, h, i, k, l, m) (Figure S1A,B), is known to be critical for efficient progression of most of the initiation steps, yet its complete structure has not been determined from any organism (reviewed in (Cate, 2017;Valasek et al, 2017)). The assembly pathway for human and N. crassa (similar in composition to human) eIF3 was recently described (Smith et al, 2016;Wagner et al, 2014;Wagner et al, 2016) but it remains to be examined for the most extensively studied S. cerevisiae eIF3 complex (Zeman et al, 2019). Recent structural studies of various PICs revealed several well-resolved but otherwise discontinuous densities attributed to various eIF3 modules that together nearly embrace the entire 40S.…”
Section: Introductionmentioning
confidence: 99%